Proyeksi Timbulan Sampah Dari Kegiatan Landfilling Di Tempat Pembuangan Akhir (TPA) Kecamatan Mandau - Nia Ramadhani Haryadi; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Landfill site is one of significant source of methane emissions into the atmosphere. The waste in landfill will be decomposed in anaerobic digestion process and produced methane (CH4) with composition of 45-60%. Methane gas has the potency as a source alternative energy of electrical energy. Production of methane gas were analyzed with LandGEM. Conversion of methane gas to electrical energy calculated by multiplication of conversion factor values with methane gas. Based on projection result weight volume analysis with in Mandau landfill area, can only accommodate the waste for forty-two months twenty-eight days. The LandGEM analysis shown that the total landfill gas from Mandau Landfill in 2021 will reach 8.575.000 m3/year equals to 978,88 m3/hour. Total methane generation will reach 5.145.000 m3/year equals to 587,33 m3/hour. Analysis of conversion methane gas to electrical energy, reached peak production after one year closure landfill site in 2021 amount 6.560 kWh.Keywords: methane, LandGEM, landfill